Konsep Penebusan dalam Kitab Rut - Sarah Wassar (Sekolah Tinggi Teologia Kerusso Indonesia, 2022)
AbstractEvery believer who wants to experience God in daily life in making important and less importantdecisions, both consciously and unconsciously. The message that was conveyed was that a man bygrace made the decision to redeem and renew a lost inheritance, and pure love removed alldifficulties. The method used to explain the meaning of redemption in the book of Ruth is a literaturestudy in the form of a literature study. Through the description of the literature review, the authorfinds the results of several biblical reviews of the concept of redemption in the book of Ruth.